A virtue ethical approach to decisional capacity and mental health. (2nd April 2016) - Ciurria, Michelle
Abstract: It is a common assumption that lack of autonomy is incompatible with decisional capacity and mental health. However, there are two general conceptions of autonomy, one value-neutral and the other value-laden, which imply different notions of mental health. I argue that the value-neutral notion of autonomy is independently inadequate and that it also provides an inadequate foundation for judging whether someone is decisionally incapable or mentally disordered. I propose an alternative, value-laden account which posits ten capabilities required for basic human functioning. I then defend this account against objections and highlight its practical utility in designing optimal treatment.